Effects of Housing Systems on Some Mineral Contents of Hen’s Eggs - SEKEROGLU, AHMET; SARI, HAYATI; MENDIL, DURALI; SARICA, MUSA (Asian Journal of Chemistry, 2010)
This study was conducted to determine the effects of housing systems on the mineral contents and shell colour of eggs. Egg samples were collected from deep litter, cage, farmyard and traditional village production systems. Egg shell colour scale in farmyard, deep litter and cage systems were found darker than traditional village system (p < 0.01). Mn contents in village eggs were found significantly higher than farmyard, deep litter and cage systems eggs (p < 0.05). However, Fe and Zn minerals in deep litter system were higher than cage, farmyard and village systems eggs (p < 0.01). Although Cu contents in deep litter system eggs were higher than cage, farm and village system eggs, Na and K contents were significantly lower. There were no important difference among the Ca and Mg contents (p > 0.05) among housing systems. There were an important relationship between egg weight and the egg shell colour (p < 0.01), there was not significant relationship between the mineral contents and the shell colour (p > 0.05). As a conclusion, it can be said that the eggs of the deep litter system were the higher quality, when the egg shell colour and the mineral elements consider together.